A flag transitive plane of order 49 and its translation complement - M. L. Narayana Rao; K. Satyanarayana; K. M. Arjuna Rao (International Journal of Mathematics and Mathematical Sciences)
The translation complement of the flag transitive plane of order 49 [Proc. Amer. Math. Soc. 32 (1972), 256-262] constructed by Rao is computed. It is shown that the flag transitive group itself is the translation complement and it is a solvable group of order 600.